OPTIMUM ECONOMIC ROTATION FOR EUCALYPTUS CAMALDULENSIS PLANTATIONS IN THAILAND - Niskanen, Anssi (วารสารวนศาสตร์ไทย, 2022)
The optimum economic rotation age for eucalypt (Eucalyptus camaldulensis Dehn.) plantations established by forest industries and small woodlot owners using intercropping with cassava (Manihor esculenta Cantz), was assessed. With a chosen of 10 % discount rate, the economic soil expectation value was maximised with a 10 year rotation age. For the evaluation of an environmental-economic optimum rotation age, on-site benefits in erosion control, costs of water and nutrient consumption, and benefits in carbon sequestration were tentatively valued. The maximum environmental-economic soil expectation value was reached with a 11 year rotation period. The optimum economic rotation age for Eucalyptus camaldulensis Dehn. in Thailand was approximately two times longer than presently applied in pulpwood production.